Intracranial Hemorrhage in a Neonate with Congenital Factor VII deficiency - Pejaver, Ranjan Kumar; Bilagi, Archana; HK, Prakash (Asian Journal of Clinical Pediatrics and Neonatology, 2018)
Congenital factor VII deficiency is a rare autosomal-recessive bleeding disorder. Clinical manifestations vary widely from asymptomatic subjects to life-theatening hemorrhages. Treatment options include fresh frozen plasma, prothrombin complex concentrates or plasma-derived FVII concentrates. We, hereby, present a case of 9 day old male neonate, admitted with multifocal seizures, lethargy, refusal to feed, and signs of raised intracranial tension. His prothrombin time was prolonged and CT head showed acute subdural hematoma with subarachnoid hemorrhage. His clotting factor assays, done in view of spontaneous intracranial hemorrhage, showed factor VII deficiency.